Adaption potential of Crassostrea gigas to ocean acidification and disease caused by Vibrio harveyi. (29th June 2020) - Nordio, Davide; Khtikian, Natalie; Andrews, Sean; Bertotto, Daniela; Leask, Karen; Green, Timothy
Abstract: The survival and development of bivalve larvae is adversely impacted by ocean acidification and Vibrio infection, indicating that bivalves need to simultaneously adapt to both stressors associated with anthropogenic climate change. In this study, we use a half-dial breeding design to estimate heritability ( h 2 ) for survival to Vibrio harveyi infection and larval shell length to aragonite undersaturated and normal conditions in laboratory-reared Crassostrea gigas . Phenotypic differences were observed between families for these traits with heritability estimated to be moderate for survival to V. harveyi challenge ( h 2 = 0.25) and low for shell length in corrosive (Ωaragonite = 0.9, h 2 = 0.15) and normal conditions (Ωaragonite = 1.6, h 2 = 0.15). Predicted breeding values for larval shell length are correlated between aragonite-undersaturated and normal conditions (Spearman r = 0.63, p < 0.05), indicating that larger larvae tend to do better in corrosive seawater. Aquaculture hatcheries routinely cull slow-growing larvae to reduce and synchronize time taken for larvae to metamorphose to spat, thus inadvertently applying size-related selection for larger larvae. This indirect selection in the hatchery populations provides a plausible explanation why domesticated oyster populations are less sensitive to ocean acidification.